133: QUALITY OF RECOVERY AFTER SUBTOTAL GASTRECTOMY USING QOR-40. (23rd April 2022) - Feenstra, M; Küçükçelebi, S; Van Berge Henegouwen, M; Hollmann, M; Gisbertz, S; Daams, F; Albersen, J; Ten Hoope, W; Hermanides, J; Eshuis, W
Abstract: Background and aim: Gastric cancer surgery highly impacts postoperative quality of life. The Quality of Recovery-40 (QoR-40) is a validated 40-item patient questionnaire, designed to evaluate the quality of recovery after anesthesia. QoR-40 is subcategorized in five dimensions; physical comfort, physical independence, psychological support, emotional state and pain. The aim of this study was to evaluate the quality of recovery after subtotal gastrectomy using the QoR-40 questionnaire and to establish a reference standard for the QoR-40 after gastrectomy to be used in future studies. Methods: This prospective observational study included all patients undergoing subtotal gastrectomy between January 2020 and December 2020 in the Amsterdam UMC. Primary endpoint was the quality of recovery on day three after surgery, using the Dutch QoR-40. Secondary endpoint was the occurrence of poor quality of recovery (PQR), defined as impairment in 2 or more dimensions, or impairment in the global QoR-40. Results: 27 Patients were included in this study, the median total score of the QoR-40 questionnaire was 184 [IQR 176–192]. Eight patients had a PQR, of whom four patients (50.0%) developed postoperative complications. Furthermore, two patients without PQR developed complications (7.4%). Impairment occurred mainly in dimensions physical comfort, physical independence and emotional state. Conclusion: This study presents a reference standard for quality of recovery based on the QoR-40 questionnaire in patients undergoing subtotal gastrectomy. PQR may be related to postoperative complications. Future studies should focus on enhancing physical comfort, physical independence and emotional state to improve patient reported quality of recovery.